Effect of Brisk Walking Exercise on Blood Sugar Levels in Prolanis Members at Community Health Center - Rochman, Mohamad Isfanur; Kurdi, Fahruddin; Kholis, Anja Hesnia (Al-Hijrah Indonesia, 2024)
Many diabetes mellitus sufferers still lack regular physical activity. Physical activity such as brisk walking can be a form of exercise that effectively controls blood sugar levels. This study aims to determine the effect of brisk walking on random blood sugar levels in Prolanis in the Kesamben Community Health Center working area, Jombang Regency. The research design uses a pre-experiment with a one-group pre-post-test design approach. The population of Prolanis members was 35 respondents, and the sample size was 20 respondents taken using non-probability purposive sampling. The independent variable is brisk walking, the dependent variable is random blood sugar levels, data collection uses the GlucoDR blood sugar checking tool, and the statistical test used is the Wilcoxon Test analysis. The research results showed that of the 20 respondents, the majority, namely 15 (75%), were in the high category before being given the fast walking treatment. On the other hand, most respondents were in the moderate category after fast walking exercise, namely 15 respondents (75%). The results of the Wilcoxon statistical test show p-value = 0.002 where p-value < α (0.05). It can be concluded that brisk walking affects random blood sugar levels. Brisk walking exercise affects changes in random blood sugar levels in Prolanis in the Kesamben Community Health Center working area, Jombang Regency. Brisk walking is recommended as a type II diabetes management therapy to control blood sugar levels because of the low side effects, and it has been proven to be effective.